Adoption of Online Marketing in the Malaysian Hotel Sector from an Organizational Innovativeness Perspective - Said, Mohd Fuaad (2007)
Online marketing is the latest Internet-based marketing medium and is well received by the hotels industry worldwide. It has beneficial features that make it useful to the industry; therefore, the Malaysian hotel industry can be expected to adopt online marketing. However, as of 2002, this was not happening, as the majority of them appeared not to have been utilizing this marketing medium. This situation invited questions as to why so few Malaysian hotels were adopting the technology.